Visualization of light-emitting diode lighting damage process in radiation environment by an in situ measurement. (1st July 2022) - Hosaka, Yuji; Nishimori, Nobuyuki; Itoga, Toshiro; Nakazawa, Shingo; Tanaka, Shinichiro; Seno, Toshio; Kondo, Chikara; Inagaki, Takahiro; Fukui, Toru; Watanabe, Takahiro; Tanaka, Hitoshi
Abstract: We investigated the radiation damage process of commercially available light-emitting diode (LED) lightings in an X-ray radiation environment such as the electron storage ring SPring-8. It was found that metal-oxide-semiconductor field-effect transistors (MOSFETs) in the LED power supplies were damaged by X-ray irradiation by a total dose effect greater than several hundred Gy (air kerma). To visualize the whole damage process, we performed in situ measurement of the MOSFET under an irradiation from an X-ray tube. The result clearly showed a sudden increase of the off-state drain current accompanied by a sharp increase of MOSFET temperature as a function of radiation dose, which eventually caused the device failure. We supposed from the result a significant increase in device lifetime by switching off the LED power supply and experimentally verified it by observing the increase of lifetime by an order of magnitude or more under the same irradiation condition.